(untitled) (Research, Society and Development, 2020)
The present study aimed to carry out an integrative review on the aging process and its relationship between sarcopenia, protein consumption and nutritional status. To select the samples, criteria for articles indexed from 2015 to 2019 published in national journals were made available in full in Portuguese and English. Data collection was carried out in the electronic databases: Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Google Scholar. The survey used the descriptors: "sarcopenia", "aging", "protein consumption" and "nutritional status". The search resulted in 24 articles by which the descriptors were affected; leaving 8 articles for analysis, interpretation and discussion, after applying the inclusion and exclusion criteria. In the studies examined, it was noticed that of all the processes that affect the human being, aging is the most natural of them, in which physiological changes occur in the organism as a whole, and that there are two types of aging described in the literature: physiological or senescence and the pathological or senility. In what follows, one of the changes that affect functionality that are related to pathological aging is sarcopenia, which is a syndrome characterized by progressive and widespread loss of muscle mass and strength, prevailing from 7% to 50% among the elderly population. Thus, it is concluded that a close relationship between protein consumption, nutritional status and sarcopenia during the aging process.